Post Liberalization Growth in TFP of Selected Indian Manufacturing Industries: A Stochastic Frontier Decomposition Analysis - Joshi, Rajesh (2010)
This dissertation establishes a stochastic frontier for six Indian manufacturing industries. Three models are established and decomposed: the cross-section model, the time invariant model and the time varying decaying model. All three models have been used to check the robustness of the results. The analysis uses CMIE data which is in panel data frame work. The major finding is that most industries have declined in their technical efficiency and Total factor productivity. The implementation has been done using STATA11.